(3cfR Gdedhc aj cjajI GdSdhcs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj deG MQQJ cJGHj GdeSei HLhgQI GdReGf aj JPcQI s
(3BNQgG (B:s
(3aJYLHJ eGdc ef GMJLGLg, hbGd dg(B: (3GaJ abO Bf dc Cf JaJj, aCaJi aj Pdc GdSf s
(3HChQGbgG JbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B157 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1519s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdCOHs